1989
DOI: 10.1007/bf00505180
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathy in human diabetic neuropathy: relationship between capillary abnormalities and the severity of neuropathy

Abstract: Clinical, electrophysiological and ultrastructural morphometric observations were made in 5 diabetic non-neuropathic patients, 5 diabetic patients with mild neuropathy and 11 diabetic patients with severe neuropathy. Capillary abnormalities were assessed in simultaneous nerve, muscle and skin biopsies and compared with results from 6 age-matched, non-diabetic control subjects. Nerve capillaries demonstrated markedly greater pathology than skin and muscle capillaries. Endoneurial capillary density was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
168
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(187 citation statements)
references
References 37 publications
15
168
0
4
Order By: Relevance
“…We have previously shown a significant microangiopathy evidenced by basement membrane thickening, reduction in luminal size, and endothelial cell hyperplasia in patients with initially minimal but progressive diabetic neuropathy (Malik et al, 2005). In patients with T2DM, we show basement membrane thickening and endothelial cell hyperplasia and hypertrophy as also reported by others (Giannini & Dyck, 1995;Malik et al, 1989Malik et al, , 2005Thrainsdottir et al, 2003;Yasuda & Dyck, 1987) without a reduction in luminal area which agrees with some (Giannini & Dyck, 1995), but not other (Dyck et al, 1985;Malik et al, 2005) studies. In the present study, in patients with T2DM, there were no evidence of microangiopathy at baseline but it developed over 11 years as a consequence of hyperglycemia and other cardiovascular risk factors (Calabek, Callaghan, & Feldman, 2014;Callaghan, Cheng, Stables, Smith, & Feldman, 2012;.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have previously shown a significant microangiopathy evidenced by basement membrane thickening, reduction in luminal size, and endothelial cell hyperplasia in patients with initially minimal but progressive diabetic neuropathy (Malik et al, 2005). In patients with T2DM, we show basement membrane thickening and endothelial cell hyperplasia and hypertrophy as also reported by others (Giannini & Dyck, 1995;Malik et al, 1989Malik et al, , 2005Thrainsdottir et al, 2003;Yasuda & Dyck, 1987) without a reduction in luminal area which agrees with some (Giannini & Dyck, 1995), but not other (Dyck et al, 1985;Malik et al, 2005) studies. In the present study, in patients with T2DM, there were no evidence of microangiopathy at baseline but it developed over 11 years as a consequence of hyperglycemia and other cardiovascular risk factors (Calabek, Callaghan, & Feldman, 2014;Callaghan, Cheng, Stables, Smith, & Feldman, 2012;.…”
Section: Discussionsupporting
confidence: 92%
“…Vessels located in the perineurium and those with a major to minor axis ratio greater than 3:1 were excluded. Quantification was undertaken using our previously established morphometric techniques (Malik et al, 1989). The lumen area was calculated by tracing the inner endothelial cell border.…”
Section: Endoneurial Capillariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each fascicle was photographed at a total magnifi-cation of 400 times using a Vickers light microscope and camera; light micrograph montages were prepared of all fascicles from each biopsy. An image analysis cursor was used to trace the fascicular area, and the endoneurial capillaries and myelinated fibres were counted directly, enabling an assessment of mean fascicular area, endoneurial capillary density and myelinated fibre density [12].…”
Section: Selection Criteriamentioning
confidence: 99%
“…Detailed neurophysiological studies in diabetic patients have shown that demyelination precedes axonal loss and that the latter may be responsible for the symptoms [8]. Whilst studies in patients with established neuropathy demonstrate a combination of demyelination and axonal degeneration of myelinated fibres and degeneration with regeneration of unmyelinated fibres [9][10][11] and endoneurial microangiopathy [12][13][14][15], the early pathological features of patients with diabetic neuropathy are not clearly defined.…”
Section: Introductionmentioning
confidence: 99%